2020
DOI: 10.3138/ptc-2019-0004
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapists Prefer Clinical Supervision to Focus on Professional Skill Development: A Qualitative Study

Abstract: Purpose: We explored physiotherapists’ perceptions of clinical supervision. Method: Individual semi-structured interviews were conducted with a purposive sample of 21 physiotherapists from a public hospital. Qualitative analysis was undertaken using an interpretive description approach. The Manchester Clinical Supervision Scale (MCSS–26) was administered to evaluate the participants’ perceptions of the effectiveness of the clinical supervision they had received and to establish trustworthiness in the qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The lower score for physiotherapy is consistent with several other studies [ 14 , 18 , 19 ]. This may be explained by other research findings where physiotherapists reported greater satisfaction when direct models of clinical supervision are used rather than a mix of direct and reflective clinical supervision [ 31 , 32 ] which was the predominant model used by physiotherapists in this study.…”
Section: Discussionmentioning
confidence: 62%
“…The lower score for physiotherapy is consistent with several other studies [ 14 , 18 , 19 ]. This may be explained by other research findings where physiotherapists reported greater satisfaction when direct models of clinical supervision are used rather than a mix of direct and reflective clinical supervision [ 31 , 32 ] which was the predominant model used by physiotherapists in this study.…”
Section: Discussionmentioning
confidence: 62%
“…It is well known that physiotherapists consider clinical supervision to be effective, especially if it favors the development of their professional skills. Indeed, the physical therapists preferred a direct supervision model, in which their supervisor directly observed and guided the development of their professional expertise [ 44 ]. Additionally, physical therapists recognized the importance of informal supervision in which guidance is provided from supervisors who appreciate the supervision process [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lower score for physiotherapy is consistent with several other studies (13,17,18). This may be explained by other research ndings where physiotherapists reported greater satisfaction when direct models of clinical supervision are used rather than a mix of direct and re ective clinical supervision (30,31) which was the predominant model used by physiotherapists in this study.…”
Section: Discussionmentioning
confidence: 64%